FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN TENAGA KERJA UNTUK BERKERJA DI KEGIATAN PERTANIAN (Studi Kasus : Kabupaten Rembang) - Khaafidh, Muhammad; Poerwono, Dwisetia (Diponegoro Journal of Economics, 2013)
The agricultural sector in Rembang district has contribution in Gross Regional Domestic Product (GRDP) Rembang district that continues to decline. Besides that, the agricultural sector also has a lower wage rate than the non-agricultural sector. However, the majority of the workforce in Rembang district actually absorbed in the agricultural sector. Therefore,it is needed to identify the cause of workers in Rembang district decided to work on agricultural activities. This study aimed to identify the factors that influence the decision of labor to work on agricultural activities in Rembang district. The method used in this study is binary logistic regression. Types of data used are primary data obtained from 100 samples workforce that has worked in Rembang district, as well as secondary data as supporting data in this study. The results of this study show the results value of McFadden R-squared at 0.760470 and value of LR stat at 90.18469. Variable of the land ownership, experience of farming, education, age and income are influence significantly to an individual's decision to work in agricultural activities in Rembang district. So that the land ownership, experience of farming, education, age and income should be considered to address the issue of employment in Rembang district.